Transportation increases circulating corticosterone levels and decreases central serotonergic activity in a sex dependent manner in Pekin ducks - M.M. Bergman; J.M. Schober; R. Novak; A. Grief; C. Plue; G.S. Fraley (Poultry Science)
Previous studies from our lab suggest that transportation of early adulthood ducks can have long lasting physiological effects. To better understand how transportation affects the ducks’ physiology, we evaluated several central and peripheral parameters. Thirty-six, 23-week-old ducks were collected at a commercial breeder facility and randomly assigned to one of three treatment groups (n = 6/sex/treatment): 1) caught and euthanized (control), 2) caught and put in a crated in the pen for 90 min (crate), or 3) caught, crated, and transported in a truck for 90 min (transport) to simulate actual transportation. Blood was collected for serum corticosterone and blood smear analyses. Brains were hemisected and each half was dissected into three brain areas: caudal mesencephalon (CM), rostral mesencephalon (RM), and diencephalon (DI). Mass spectrometry was run on the right half of the brain, and gene expression of TPH1, TPH2, TH, CRH, and NPY were measured on the left half of brain using qRT-PCR. Serum corticosterone levels were increased (p = 0.01) in crated hens and in transported hens and drakes (p = 0.0084) when compared to control. HLR was increased (p = 0.035) in crated hens and transported hens and drakes compared to control. No differences in serotonin turnover were observed in drakes but increased in hens within the CM and RM from control to crate (p = 0.01) and crate to transport (p = 0.016). There were no differences in DA turnover or in gene expression for all brain areas for drakes and CM and RM for hens. Within the DI, hens showed a decrease (p = 0.03) in TPH1 for transport compared to crate. Overall, transportation elicits an acutely stressful event that increases corticosterone and HLR in a sex dependent manner where hens appear to be more reactive to the stressor than drakes. Our data supports that when assessing a stress response, care must be given to the sex of the bird and to the relative timepoint of sampling compared to the perceived onset of the stressor.